(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
This article discusses the importance of teaching English and the role of games in teaching young learners, with giving examples of games how it is beneficial. It was determined from the data that games should be employed in second language learning classrooms in terms of providing an atmosphere for EFL learners in which there are fun, motivation and high learning performance.